When is it appropriate to reprimand a norm violation? The roles of anger, behavioral consequences, violation severity, and social distance - Kimmo Eriksson; Per A. Andersson; Pontus Strimling (Judgment and Decision Making, 2017)
Experiments on economic games typically fail to find positive reputational effects of using peer punishment of selfish behavior in social dilemmas. Theorists had expected positive reputational effects because of the potentially beneficial consequences that punishment may have on norm violators' behavior. Going beyond the game-theoretic paradigm, we used vignettes to study how various social factors influence approval ratings of a peer who reprimands a violator of a group-beneficial norm. We found that ratings declined when punishers showed anger, and this effect was mediated by perceived aggressiveness. Thus the same emotions that motivate peer punishers may make them come across as aggressive, to the detriment of their reputation. However, the negative effect of showing anger disappeared when the norm violation was sufficiently severe. Ratings of punishers were also influenced by social distance, such that it is less appropriate for a stranger than a friend to reprimand a violator. In sum, peer punisher ratings were very high for a friend reprimanding a severe norm violation, but particularly poor for a stranger showing anger at a mild norm violation. We found no effect on ratings of whether the reprimand had the beneficial consequence of changing the violator's behavior. Our findings provide insight into how peer punishers can avoid negative reputational effects. They also point to the importance of going beyond economic games when studying peer punishment.